Optimasi Waktu Aplikasi Dan Jenis Trichoderma Terhadap Pertumbuhan Tanaman Jagung Dan Perkembangan Penyakit Hawar Pelepah (Rhizoctonia Solani) Pada Jagung Varietas Lokal Momala - Rida Iswati; Nurul Khozib; Angry Pratama Solihin; Asnawi Asnawi (Universitas Gadjah Mada, 2025)
Maize sheath blight disease caused by Rhizoctonia solani is one of the important maize plant diseases and threatens the potential of local maize production. One of the control efforts is with the biological agent Trichoderma. The type and time of application of Trichoderma are the keys to effective control. This study aims to identify the combination of treatments between the type and time of optimal Trichoderma application. This study was conducted using a Completely Randomized Design (CRD) with a treatment combining the type of Trichoderma (T1 = T. asperellum TZ11MO1, T2 = T. harzianum) with the treatment time (W1 = before planting, W2 = after planting) so that the combination of treatments becomes T1W1, T1W2, T2W1, T2W2 added with positive (K+) and negative (K-) controls and repeated four times. The results showed that the combination of treatments of the type and time of application of Trichoderma had the same effect on the growth of maize plants and the T1W1 treatment showed the best effect as a biological agent on the incubation period, disease incidence and intensity of R. solani sheath blight disease attacks on the Momala variety.